Faktor – Faktor yang Berhubungan dengan Strategi Koping pada Pasien Kanker Payudara (Ca Mammae) yang Menjalani Kemoterapi di RS Urip Sumoharjo Bandar Lampung - Ria Septia Ningsih; Riska Hediya Putri (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Breast cancer is one of the types of cancer with the highest incidence in women in Indonesia. One of the therapies commonly used in breast cancer management is chemotherapy, but this procedure often causes stress and has an impact on reducing the quality of life of patients. Therefore, effective coping strategies are needed so that patients are able to adapt and face the conditions of the disease they experience. Several factors suspected to be related to coping strategies in breast cancer patients undergoing chemotherapy include the stage of the disease, the duration of cancer, and family support. Data shows that the number of breast cancer patients in Lampung Province reached 572 people, while at Urip Sumoharjo Hospital, there were 1,949 patients recorded in 2024. This study aims to analyze factors related to coping strategies of breast cancer patients undergoing chemotherapy at Urip Sumoharjo Hospital, Bandar Lampung. This study is a quantitative study with a cross-sectional approach. The sampling technique used was accidental sampling. The research instruments included a questionnaire on respondent characteristics, a questionnaire on family support, and a questionnaire on coping strategies. The population in this study was all 162 breast cancer patients undergoing chemotherapy at the hospital, with a sample size of 62 respondents. Data collection was conducted using a questionnaire, while data analysis used the Chi-Square test and the Gamma test. The results showed that the majority of respondents were in stage IV, with 41 respondents (66%). The duration of the disease was mostly in the 2–4 years range, with 29 respondents (47%). Family support was predominantly supportive, with 60 respondents (97%), and adaptive coping strategies were also found in 60 respondents (97%). The analysis showed a significant relationship between the studied variables and the coping strategies of breast cancer patients, with a p-value of 0.001 at the 95% confidence level. Based on these findings, nurses and hospitals are expected to continue providing motivation and support to breast cancer patients undergoing chemotherapy to improve their quality of life.